IDENTITY REPRESENTATION IN THE ARCHITECTURE OF NAHDLIYIN MOSQUES IN MALANG RAYA, EAST JAVA - Eka Putrie, Yulia
(Mosque) architecture in various parts of the world throughout history shows a strong relationship between identity representation phenomena and various sociopolitical dynamics. A mosque is basically a locus of articulation for its community’s religious values, beliefs, and views. In the context of Indonesia, where the diversity of Islamic thoughts and sub-cultures takes place, mosques have however become more than a religious space. Each Islamic group tries to assert their respective authority and identity in a mosque, making it a political space. Numerous sociopolitical issues emerged as a result of the dynamic interactions between Islamic groups in the community mosques over the past few decades. One of the most important socio-political issues is the conflict caused by the expropriation attempts on mosques. Identity representation phenomena that occur in the architecture of the Nahdliyin mosque were indicated as related to these socio-political issues. This study aims to explore patterns and strategies for identity representation in the architecture of the community mosques, especially the Nahdliyin mosques, and its relation to the local socio-political context. The nature of this exploratory research leads to preliminary research before determining the Grounded-theory research as the appropriate method for the main research. The Grounded-theory research method is used as the main research method due to its flexibility to develop cases or object of study based on the need to construct substantive theories. Its series of structured analysis procedures provide ways to identify the diversity and complexity of the pattern in the process of action - interaction grounded on the experience and intersubjective views of the community. The research has concluded that efforts to represent identity were taken not only through identity affirmation strategies both explicitly and implicitly, but also by means of identity disaffirmation through the modification, elimination, or imitation of architectural elements. Architectural elements that represent identity have ideological, cultural, and political meanings that are important for each Islamic group or sub-culture. Resistance and negotiation towards these architecture elements of mosque indicate the importance of them as the elements of identity representation. Furthermore, the elements of identity representation are also used to reveal or to conceal affiliative identities in community mosques. Most of the affiliated community mosques, especially the Nahdliyin mosque, take implicit identity affirmation strategies by utilizing various iconographic elements and symbolic elements to communicate their affiliative identity. Meanwhile, in nonaffiliated community mosques, the identity elements of each group experienced negotiations as well as resistance until a common understanding or agreement was reached. Apart from the different patterns and strategies adopted in these community mosques, there is a shared awareness of the socio-political issues that are considered important. Different patterns and strategies for the identity representation of identity in mosque architecture were found as a way of conflict prevention in order to create a peaceful and tolerant religious environment. The contribution of this research is to propose a substantive theory in the architectural discourse regarding identity affirmation – disaffirmation and its relationship with conflict prevention in public spaces. Furthermore, understanding the interactions and conflicts is important to comprehend the relationship between people and places. In certain contexts, public space can be a locus for political contestation between community groups. The dynamics of interaction can lead to the dynamics of people – place relationship. Other than causing stronger attachment between people and place (place-attachment), interactions and conflicts can also result in place-detachment. Place-detachment can arise in situations where all negotiation and resistance end with a place that is no longer representative for a particular community. In this study, place-detachment is also one way of conflict resolution. People release all attachments to a place as a way out in the middle of a deadlock in the interaction process.